Measuring health insurance literacy in the Netherlands – First results of the HILM-NL questionnaire. Issue 11 (November 2022) - Holst, Laurens; Rademakers, Jany J.D.J.M.; Brabers, Anne E.M.; de Jong, Judith D.
Highlights: There is a wide variation in Health Insurance Literacy among Dutch citizens. Level of education and household net-income are related to Health Insurance Literacy. Supporting vulnerable groups in choosing/using a health insurance policy is important. Abstract: Background: There are several indications that citizens in the Netherlands struggle to make critical, well-considered decisions about which insurance policy best fits their needs and preferences. This can lead to citizens being sub-optimally insured, facing unexpected costs or suffering inadequate coverage. This study aims to examine how health insurance literacy (HIL) is distributed among citizens in the Netherlands; and to find out whether there are certain groups who have more difficulty choosing and using a health insurance policy. Methods: We measured health insurance literacy using the HILM-NL questionnaire, the validated Dutch version of the original health insurance literacy measure (HILM). In February 2020, the HILM-NL was sent to 1, 500 members of the Nivel Dutch Health Care Consumer Panel. The response rate was 54% (806). Results: There is a wide variation in HIL among citizens in the Netherlands. The average total HILM-NL score is 55.14 (on a range of 21–84). The level of education and the household net income are significantly related to HIL. Conclusions: Citizens who completed less education or earn a lower income are relatively more likely to have difficulty choosing a health insurance policy or using policy benefits to pay for health services once enrolled. It is important to support these vulnerable groups properly in their choice and use of a health insurance policy.